Immigrant key workers: Their contribution to Europe's COVID-19 response - Francesco Fasani; Jacopo Mazza (Institute of Labor Economics (IZA), 2020)
This note describes the contribution of migrant workers to the ongoing effort to keep basic services running in the Union during the COVID-19 epidemic. We quantify the prevalence of migrant workers in the so called "key professions" that the Commission and Member States have identified using the most recent wave of the EU Labour Force Survey. Our results show that migrant "key workers" are essential for critical functions in European societies.
Keywords: F22; J61; K37; 330; migrant workers; COVID-19 epidemic; key occupations